Radiation effects produced by the intra-articular injection of 32P - Ubios, A. M.; Cabrini, Rómulo Luis; Silberman, F. S.; Miranda, F. F. (J. B. Lippmcott Company, 1978)
Fil: Ubios, A. M. Comisión Nacional de Energía Atómica; Argentina